1971
DOI: 10.1111/j.1469-7998.1971.tb01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the pituitary gland of some members of the suborder Suiformes (Mammalia: Artiodactyla)

Abstract: The macroscopical and microscopical anatomy of the pituitary gland of the warthog (Phacochoerus aethiopicus) is described and compared with that of the Vietnam pig (a domestic race of Sus scrofa). The glands of the two animals differ considerably in shape but agree in anatomical details. The morphological and histochemical characteristics of cells of the pars distalis are described in the warthog, bush pig (Potamochoerus porcus), Vietnam pig (all members of the family Suidae) and hippopotamus (Hippopotamus amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Application of this method to the viscacha pituitary and those of other species (unpublished observations) has confirmed the validity of this method as a pituitary stain. Furthermore it was found that the type 1 cells can be specifically stained by luxol fast blue in the LB/PAS/OG method (Plate V (b)), an observation similar to those made in other species (mink-Weman, 1970; some members of Suiformes - Allanson, 1971 ; leaf-nosed bats -Patil, 1974). In addition to the above reason, the type 1 cells were distinguished as somatotrophs and the type 2 as prolactin cells since the former display no differences in size and frequency between immature, mature, pregnant or lactating animals, whereas the latter were apparently larger and more numerous in the pregnant and lactating females examined (see Table 111).…”
Section: Plate 1vsupporting
confidence: 77%
“…Application of this method to the viscacha pituitary and those of other species (unpublished observations) has confirmed the validity of this method as a pituitary stain. Furthermore it was found that the type 1 cells can be specifically stained by luxol fast blue in the LB/PAS/OG method (Plate V (b)), an observation similar to those made in other species (mink-Weman, 1970; some members of Suiformes - Allanson, 1971 ; leaf-nosed bats -Patil, 1974). In addition to the above reason, the type 1 cells were distinguished as somatotrophs and the type 2 as prolactin cells since the former display no differences in size and frequency between immature, mature, pregnant or lactating animals, whereas the latter were apparently larger and more numerous in the pregnant and lactating females examined (see Table 111).…”
Section: Plate 1vsupporting
confidence: 77%
“…This is not the case for other modern suid genera, which have only been partly documented (Anthony and Grzybowski 1931). The external morphology of the brain of modern Tayassuidae is also described in very few works (Krueg 1878;Allanson 1971;Saraiva 2017). To our knowledge, there is no documentation of a fossil suoid endocast in the literature.…”
Section: Endocasts Of Modern Artiodactyl Groupsmentioning
confidence: 98%